DETERMINAN NIAT MEMBELI MAKANAN HALAL SECARA ONLINE DI INDONESIA: INTEGRASI UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) DAN THEORY OF PLANNED BEHAVIOR (TPB) - Lestari, Nurrizka Puji; Wahab, Abd.; Widiastuti, Tika (Universitas Negeri Surabaya, 2025)
This study aims to analyze the factors influencing the intention to purchase halal food through online platforms among Generation Z in Indonesia. The research is based on data from 145 respondents, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that facilitating conditions and social influence do not significantly affect attitude, although social influence has a significant impact on purchase intention. Performance expectancy significantly influences both attitude and intention, while effort expectancy significantly affects attitude but not intention. Overall, attitude has a significant impact on purchase intention. Based on these findings, Shopee Barokah should enhance its performance by ensuring the platform is user-friendly through optimized interface design and the addition of features that simplify the purchasing process. Moreover, advertisements featuring influencer reviews can be strengthened to leverage the significant effect of social influence on purchase intention. Ensuring smooth technological and infrastructural support such as responsive customer service, secure payment methods, and fast delivery can further boost Generation Z’s intention to shop on the platform.